2013
DOI: 10.1111/jce.12311
|View full text |Cite
|
Sign up to set email alerts
|

Differential Clinical Characteristics and Prognosis of Patients with Longstanding Persistent Atrial Fibrillation Presenting with Recurrent Atrial Tachycardia versus Recurrent Atrial Fibrillation After First Ablation

Abstract: LS-AF patients who develop R-AT versus R-AF after first ablation have more favorable baseline characteristics and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…[1] While lesions for AFL/AT with identifiable mechanisms are mostly limited to the critical isthmus. Previous studies also reported less favorable outcome of RFCA for patients with recurrent AF than AT, [12,13] which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…[1] While lesions for AFL/AT with identifiable mechanisms are mostly limited to the critical isthmus. Previous studies also reported less favorable outcome of RFCA for patients with recurrent AF than AT, [12,13] which is consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…4,5 In contrast, patients with persistent and long-standing persistent AF treated with a more targeted ablation strategy (PVI with or without documented non-PV trigger ablation) are more likely to experience arrhythmia recurrences in the form of AF instead of OATs. However, when the arrhythmia recurrence in these patients is paroxysmal in nature, this likely suggests a favorable modification of the underlying AF substrate, which becomes less capable of sustaining AF.…”
mentioning
confidence: 99%
“…17 During the second ablation procedure, more recurrent atrial tachycardia had clear targets than recurrent atrial fibrillation and had more favourable prognosis. 18 Atrial fibrillation with pulmonary vein trigger had clear target, and pulmonary vein isolation was effective. It was difficult in identifying and mapping the non-pulmonary vein triggers during the procedures, and the exact mechanisms by which linear and complex fractionated atrial electrograms ablation eliminated atrial fibrillation and prevented recurrence were not fully understood.…”
Section: Discussionmentioning
confidence: 99%